THE IMPORTANCE AND NECESSITY OF ECONOMIC DIAGNOSTICS IN THE MANAGEMENT OF A HIGHER EDUCATION INSTITUTION - Jo‘rayev Soxibjon Nodirbek o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article examines the characteristics of a higher education institution as an object of economic diagnostics. The role of economic diagnostics in ensuring the efficiency of the higher education institution and the importance of diagnostic principles in management are highlighted. Approaches to the evaluation of the quality of higher education are based on the results expected by the subjects interested in the educational process. A scientific conclusion and practical recommendations related to the economic assessment of the quality of higher education are given.